The caller ebook - Fossum, Karin (Inspector Sejer, 2023)
"Pranks can have lethal consequences, even when they seem harmless to start with. . . . A poison bonbon that ranks with the best of Ruth Rendell." —Stephen King in  Entertainment Weekly One mild summer evening, a young couple are enjoying dinner while their daughter sleeps peacefully in her stroller under a tree. When her mother steps outside she is stunned: the child is covered in blood. Inspector Sejer is called to the hospital to meet the family. Mercifully, the child is unharmed, but the parents are deeply shaken, and Sejer spends the evening trying to understand why anyone would carry out such a sinister prank. Then, just before midnight, somebody rings his doorbell. No one is at the door, but the caller has left a small gray envelope on Sejer's mat. From his living room window, the inspector watches a figure disappear into the darkness. Inside the envelope Sejer finds a postcard bearing a short message: Hell begins now. Praise for Karin Fossum: "A superb writer of psychological suspense." — New York Times "Sejer is a beautifully created character, a thoughtful, lonely man with great empathy." — Publishers Weekly "With sharp psychological insight and a fine grasp on police procedure, Fossum is easily one of the best new imports the genre has to offer." — The Baltimore Sun "No one can thoroughly chill the blood the way Karin Fossum can . . . will put you away, no questions asked."— Los Angeles Times "Fossum . . . writes like Ruth Rendell with the gloves off." — Kirkus Reviews "A truly great writer and explorer of the human mind." —Jo Nesbo, New York Times bestselling author of the Harry Hole series